Intravitreal injection of ranibizumab (Lucentis) versus pan-retinal photocoagulation as a preoperative adjuvant before vitrectomy in management of proliferative diabetic retinopathy - Mohammed S Ahmed (Journal of Medicine in Scientific Research, 2021)
Background Diabetic retinopathy is a microvascular complication of diabetes mellitus, and it is the most common ophthalmic complication. Pan-retinal photocoagulation (PRP) has been the standard treatment for proliferative diabetic retinopathy (PDR) and can be used as an adjuvant before vitrectomy but has adverse effects. The use of intravitreal ranibizumab has been suggested as an alternative treatment or an alternative adjuvant before vitrectomy. Aim This study was conducted to study the effect of intravitreal injection of ranibizumab 10 mg/ml (Lucentis) versus PRP as an adjuvant before vitrectomy in the management of PDR. Patients and methods This study was performed on 40 eligible eyes, which were allocated into two groups: group A included 20 eyes that were injected by ranibizumab 10 mg/ml (Lucentis) intravitreally 4–7 days before vitrectomy and group B included 20 eyes that received argon laser photocoagulation (PRP) 1 month before vitrectomy. Results The study revealed highly statistically significant difference between both groups regarding the incidence of intraoperative bleeding, with patients in the PRP group showing less intraoperative bleeding, a lower need for intraoperative use of diathermy, a lower need for intraoperative use of both blunt and sharp dissection, as well as a need for a lower number of endolaser shots when compared with patients in the intravitreal injection of ranibizumab group. It can be concluded that treatment with ranibizumab was not associated with a higher incidence of postoperative bleeding or complications than PRP at 6 months postoperatively among eyes with PDR and that ranibizumab may be an appropriate alternative adjuvant for patients with PDR. However, more studies with longer-term follow-up are recommended to complement the current study results and demonstrate real clinical differences between the two adjuvant treatments. Conclusion Using both adjuvants before vitrectomy enhances vitrectomy outcome when best indicated rather than without using. The shorter time of surgery and less endodiathermy or endolaser use is with the PRP group, although postoperative best-corrected visual acuity gaining is not significant. So, real clinical differences between the two adjuvants need more research studies.